1972
DOI: 10.1172/jci107090
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Reperfusion

Abstract: A B S T R A C T The effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Although today it is unequivocally clear that timely reperfusion of an occluded coronary artery is the only way to rescue myocardium from impending infarction, this notion is a little more than 40 years old and goes back to the study by Ross and collaborators 39,40 who first reported that reperfusion after 180-minute coronary occlusion reduced infarct size in dogs. These findings were quickly translated to humans with acute myocardial infarction who were reperfused by thrombolysis or percutaneous coronary interventions (PCIs).…”
Section: Coronary Circulation As a Determinant Of Reperfusion And Repmentioning
confidence: 99%
“…Although today it is unequivocally clear that timely reperfusion of an occluded coronary artery is the only way to rescue myocardium from impending infarction, this notion is a little more than 40 years old and goes back to the study by Ross and collaborators 39,40 who first reported that reperfusion after 180-minute coronary occlusion reduced infarct size in dogs. These findings were quickly translated to humans with acute myocardial infarction who were reperfused by thrombolysis or percutaneous coronary interventions (PCIs).…”
Section: Coronary Circulation As a Determinant Of Reperfusion And Repmentioning
confidence: 99%
“…The crucial importance of early reperfusion in the limitation of contractile dysfunction and irreversible ischemic damage has been clearly demonstrated [21]. Dogs submitted to reperfusion even up to 6 hours after coronary occlusion showed smaller infarct size than dogs submitted to chronic coronary occlusion [2].…”
Section: Reversible Ischemia: Patterns Of Cardiac Survivalmentioning
confidence: 99%
“…1 However, reperfusion itself can paradoxically cause additional injury; a phenomenon termed 'reperfusion injury'. 2 Reperfusion injury may cause myocardial Microvascular obstruction (MVO), which prevents sufficient myocardial tissue perfusion despite complete coronary artery revascularisation.…”
Section: Introductionmentioning
confidence: 99%